Growth inhibition of different pathogenic fungi by Actinomycetes and its identification by 16S rRNA - U.R. SANGLE; O.M. BAMBAWALE, MADHUBAN GOPAL, EKTA MISHRA, SUBRATA K. DAS, S.C. CHATTERJEE (Indian Phytopathology, 2010)
Actinomycete strain S1 has shown potential for being developed as a suitable biological agent for controlling the pathogenic fungi namely Rhizoctonia bataticola, Fusarium oxysporum and Colletotrichum falcatum. Actinomycete S1 was identified by 16S rRNA as Streptomyces albidoflavus. Methyl ester of heptadecenoic acid has been identified to be present in actinomycete strain S1 by GC/MS/MS.